CONVIVIALITY AND BECOMINGS WITH-IN DIFFERENCE. MORE-THAN-HUMAN RELATIONSHIPS IN CANDOMBLÉ - Daniela Calvo (Etnografia Polska, 2022)
In Candomblé, existence and the continuation of life are dependent on a complex dynamic of interactions involving humans and non-humans (objects, artifacts, the environment, animals, plants, minerals, the ancestors, spiritual beings, forces). It is an ontological monism, based on the concept of àṣẹ, the life force that constitutes life in its manifestations; a conception of human beings as a composition of spiritual and material components (in which ancestors, elements of nature and divine particles participate); ways of communicating and connecting with natural phenomena, the ancestors and the spiritual world; the forms of conceiving of, living with and treating health and disease; and ways of making kin all express a mode of existence, of inhabiting the world and developing along lines of life in which all more-than-human beings participate.